Psychodidae (Diptera) of Azerbaijan and Georgia - faunistics with biodiversity notes - Ježek, Jan; Manko, Peter; Oboňa, Jozef (ZooKeys, 2021)
Records of 46 Psychodidae (Sycoracinae 1, Trichomyiinae 1, Psychodinae 44) species/subspecies are presented in this paper based on specimens collected by sweep-netting in Azerbaijan and Georgia in 2019. Nine species are recorded for the first time since their original description; 12 species are new for Transcaucasia; 22 species are new for Azerbaijan; and 17 species are new for Georgia. Saraiella ressli montana Ježek, 1990 is proposed as a synonym of S. ressli Wagner, 1983, syn. nov. Knowledge of some aspects of the ecology and biogeography of selected (especially rare) species has been expanded and a clear pattern was found in species richness, rare species, and new records in relation to land use, habitat diversity, and preservation of the environment surrounding the sampling site.
Keywords: moth flies; Biodiversity; zoogeography; taxonomy; faunistics; new synonymy; Caucasus; new records